DEVELOPMENT OF CONTEXTUAL TEACHING LEARNING (CTL) LEARNING MODEL BASED ON BLENDED LEARNING PPKn LEARNING IN CLASS IV SDN 060901 MEDAN POLONIA - Eliana Purba; Daulat Saragi; Zulkifli Matondang (SENSEI RESEARCH CENTER, 2022)
This study aims to: (1) look at the CTL learning model based on Blended Learning in PPKn learning in class IV SDN 060901 Medan Polonia in the form of CTL Model Syntax based on Blended Learning, RPP in accordance with the CTL model based on Blended Learning, PPT learning media, LKPD and Learning Outcomes Test. (2) Testing the effectiveness of the CTL model based on Blended Learning PPKn learning in class IV SDN 060901 Medan Polonia. This type of research is development research using the ADDIE model, namely Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were fourth grade students at SDN 060901 Medan Polonia for the 2021/2022 academic year which opened 30 students. 1) The Feasibility Instruments used are the results of the questionnaire expert validation of the CTL learning model based on Blended Learning by 80%, the validation of the learning media experts by 93%, the RPP expert validation by 93%, the LKPD expert validation by 94% and the Learning Outcomes Test conducted by the results of the validation of N = 30 students, the r table value shows the number 0.361, the results of the reliability of the questions are 0.844 and the results of the teacher's response are 91.6% and the results of student responses are 96%. With these results the CTL model based on Blended Learning PPKn learning in class IV SDN 060901 Medan Polonia is said to be